Linking market sensing capability, innovation speed, organizational learning and marketing performance in the disruption era / Lalu Edy Herman - Herman, Lalu Edy (2019)
Tourism is a leading sector developed in Indonesia and significant contributes to the economic growth for the country's development. The development of tourism in Indonesia will have a direct impact on the community to participate in the provision of the tourism industry to meet the needs of tourists, especially the culinary and souvenir fields through small and medium enterprises (SMEs). The SMEs have a very important role in the economic development in every country, including in Indonesia. This SMEs also helps the country in creating new jobs that can support the household income. The competitiveness of SMEs is one of the key factors in efforts to increase tourism investment. Thus, it is expected that SMEs in tourism can grow, develop and be able to attract foreign investment in their businesses.